Model Grosse Akta Pengakuan Hutang Dalam Perspektif Perlindungan Kreditur(Studi Kasus Pada Lembaga Keuangan Bumn / Bumd Di Kabupaten Klaten) - Warsito , Lilik (2012)
The puposes of this study are (1). To know the Implementation of payable Agreement on financial institutions in the District of Klaten; (2). To find out the Guarantee agreement on the implementation of financial institutions in the District of Klaten; (3). To the determine the settlement of debts and receivables if the debtor default on financial institutions in the District of Klaten; (4). To analyze the most Appropriate models for the Grosse Deed of Recognition to protect the interest payable creditors. This research is juridical empiric. Research site is in PT. BRI (Persero) Tbk. Cawas Unit office, the National Credit District Pedan, Klaten Market Bank, Gondangwinangun Pawnshop. Data collection methods used was interviews and Literature study. Analysis of the data used is a qualitative analysis. The result of this study are (1). The implementation of agreements on the lending financial institutions in the District of Klaten with various titles agreements, Namely the Credit Agreement, the Agreement debt and claims, recognition of debt And claims, recognition of debt under the hand, but the essence is the lending agreement, (2). The conduct of the agreement guarantees to financial institutions in the District of Klaten is done the deed and mortgage deed granting fiduciary, but still found that the guarantee agreement is no longer valid, the agreement to transfer ownership of trust (fiduciary / fiduciare). (3). Settlement of payables and receivables if the debtor default on financial institutions in the District of Klaten is still much to be resolved in accordance with the laws do not guarantee/execution of the applicable law, with sales under the hand, re-scheduling, insurance claims, (4). Grosse Model Deed of Acknowledgement of debt to protect the interest of creditors, consisting of two models those are guaranteed to move, and secured with no moving objects.